The secret life mosses - Jensen, Lawrence; Chung, Andrew (New Zealand : ETI ; Dr. Lawrence Jensen, 2002)
Computer animations take you inside a clump of moss plants to illustrate external structure. You are then transported inside the tips of male and female stems where gametangia (sex organs), sperm release, fertilisation and embryo development are illustrated
Title from title screen
Editors, Andrew Chung, Richard Smith ; animation, Andrew Chung ; camera, Graeme Henderson, Richard Smith
Narrator: Richard Smith
Keywords: Mosses -- Anatomy; Mosses